2015
DOI: 10.7314/apjcp.2015.16.11.4671
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Cytotoxic Activities of Essential Oil from Moringa oleifera Seeds on HeLa, HepG2, MCF-7, CACO-2 and L929 Cell Lines

Abstract: Moringa oleifera Lam. (Moringaceae) is widely consumed in tropical and subtropical regions for their valuable nutritional and medicinal characteristics. Recently, extensive research has been conducted on leaf extracts of M. oleifera to evaluate their potential cytotoxic effects. However, with the exception of antimicrobial and antioxidant activities, little information is present on the cytotoxic activity of the essential oil obtained from M. oleifera seeds. Therefore, the present investigation was designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 33 publications
3
41
0
2
Order By: Relevance
“…However, recent study results found that the ethanol extract of M. oleifera seeds had no significant effect in inhibiting the proliferation of breast and colorectal tumour cells [63]. Nevertheless, a recent study observed a cytotoxic effect of M. oleifera oil in several cancer cell lines [64]. …”
Section: Phytochemistry and Medicinal Usesmentioning
confidence: 99%
“…However, recent study results found that the ethanol extract of M. oleifera seeds had no significant effect in inhibiting the proliferation of breast and colorectal tumour cells [63]. Nevertheless, a recent study observed a cytotoxic effect of M. oleifera oil in several cancer cell lines [64]. …”
Section: Phytochemistry and Medicinal Usesmentioning
confidence: 99%
“…The in vitro cytotoxic effects of LLE extract were evaluated using the standard MTT assay [24,25]. The method depends on the reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) by mitochondrial dehydrogenases in living cells.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Perkembangan yang pesat dalam bidang isolasi dan identifikasi senyawa fitokimia meningkatkan trend penelitian selama dua dekade terakhir ini terhadap pengobatan yang menggunakan tanaman herbal sebagai sumber potensial untuk agen antikanker (Awodele et al, 2012;Elsayed et al, 2015). Studi farmakologis menunjukkan bahwa ekstrak herbal terdiri dari nutrisi penting, beberapa kandungan senyawa yang memiliki aktivitas antitumor, antioksidan dan antimutasi dengan berbagai target yang saling bekerja secara sinergis (Kalappurayil and Joseph, 2017;Leone et al, 2015).…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini menunjukkan bahwa ekstrak etanol, fraksi etil asetat dan nheksan daun M. oleifera bersifat sitotoksik terhadap sel kanker payudara T47D dengan nilai IC50 yang berbeda-beda. Berdasarkan nilai IC50-nya, maka fraksi etil asetat merupakan fraksi yang paling sitotoksik.Sejumlah penelitian terhadap sel kanker yang berbeda sudah melaporkan aktivitas sitotoksik dari ekstrak M. oleifera Elsayed et al, 2015,. melaporkan nilai IC50 ekstrak M Tiloke et al, 2013)…”
unclassified